A Survey of the Character of Bung Hatta University Based on its Islamic Education Learning Program in the Digital Age - Muslim, Muslim; Effendi, Heri; Pebriyenni, Pebriyenni; Nursi, M.; Aisyah, Siti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Education throughout its history has always been intended as a vehicle to prepare the regeneration of students, so that they can carry out their life in a wise and fulfilling way. The demoralization and dehumanization that occurs in student life is attributed, among other things, to lack of honesty, distrust, lack of sense of responsibility, lack of discipline, and lack of self-integrity. This study aims to describe the PAI (Pendidikan Agama Islam - Islamic Education) learning process in the PPKn (Pendidikan Pancasila dan Kewarganegaraan - Pancasila and Civics Education) Study Program at the Bung Hatta University. This study uses a qualitative case study approach. The research subjects are PAI lecturers, Kebunghataan (Bung Hatta inspired ideals) lecturers and all of the students in the PPKn study program. Techniques of data collection used include observation, interviews and documentation studies. Data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that the PAI learning process in the PPKn Study Program at Bung Hatta University was carried out by referring to the curriculum that applies at Bung Hatta University and the study program. In writing, it has not been integrated with the idea of Kebunghataan. The implications of the above is that students who graduate from this program embody the qualities of Bung Hatta Universityâ€™s ideals, namely,Â politeness, honesty, thrifty, and dignity.